EFEKTIFITAS METHODE CUSTOMER SATISFACTION INDEX DALAM MENGUKUR KEPUASAN PELANGGAN PADA PT SSN JAKARTA - D Purnomo (POLITEKNIK LP3I JAKARTA, 2023)
This research was conducted to determine the effectiveness of the customer satisfaction index method in measuring the level of customer satisfaction at PT SSN. MSCI is a method that measures the level of overall satisfaction with an approach that considers the level of importance and level of satisfaction. Measurement is a series of activities that aim to determine the value of a quantity in the form of numbers (quantitative). Customer satisfaction is a result of a comparison between expectations of the performance obtained after using a product or service. Indicators of customer satisfaction consist of; product security, product handling on delivery, service (service), ease of obtaining products and product information. In this study, the authors used qualitative research methods, where data collection techniques were carried out through direct observation, namely collecting data by directly dealing with the research object by giving questionnaires and also interviews, namely collecting data by asking directly to related parties. Based on the results of calculations using the customer satisfaction index method, it can be concluded that PT SSN's customer satisfaction level is very satisfied with the services provided, this is evidenced by the acquisition of a CSI score of 81.8. The effectiveness of the Customder Performance Index (MCSI) method in measuring customer satisfaction is very useful and useful for PT SSN Jakarta, because it can determine the level of customer satisfaction and can make anticipation in order to maintain customer loyalty and become an effective and efficient marketing tool.Keywords: Customer Satisfaction Index Method, Measurement, Customer Satisfaction.